Tongue Displacement Device in Decreasing the Radiation Dose to Tongue and Preventing Proton Beam Overshoot in Proton Therapy for Unilateral Head and Neck Cancer - Hong, Chae-Seon; Oh, Dongryul; Ju, Sang Gyu; Ahn, Yong Chan; Kim, Yeong-bi; Park, Seyjoon; Lee, Woojin (Frontiers in Physics, 2021)
The aim of this study was to evaluate the dosimetric characteristics of a semi-customized tongue displacement device (scTDD) fabricated using a 3D printer for patients receiving unilateral head and neck irradiation with intensity-modulated proton therapy (IMPT) and assess its feasibility as a proton beam stopper compared to a standard mouthpiece (sMP). Seven consecutive patients, three with tonsil cancer, and four with oral cavity cancer were included in this retrospective study. Planning computed tomography (CT) images of each patient were acquired for each device. Both the scTDD and sMP plans were generated using a single-field optimized IMPT. The clinically relevant dose-volume parameters for the organs at risk (OARs), especially the tongue, were compared between the scTDD and sMP plans. Additionally, to assess the feasibility of scTDD as a proton beam stopper, the dose to the contralateral oral mucosa (COM) was compared with that from sMP use. The use of scTDD resulted in a statistically significant decrease in the radiation dose to the tongue and COM compared to sMP. The median mean dose to the tongue was significantly reduced with scTDD (18.3 Gy(RBE)) compared to the sMP (22.9 Gy(RBE)) (p = 0.016). The percentages of tongue volume receiving doses between 15 and 60 Gy(RBE) were significantly lower with scTDD. In the COM, scTDD resulted in a significantly lower median mean (2.9 Gy(RBE) vs. 7.9 Gy(RBE), p = 0.018) and maximum dose (39.1 Gy(RBE) vs. 41.6 Gy(RBE), p = 0.018) doses compared to sMP. The scTDD effectively decreased the radiation dose to the tongue compared to sMP in patients undergoing unilateral head and neck irradiation with IMPT and acted as a proton beam stopper to protect normal tissues located behind the target volume, such as the COM.